Multicellular Quadruple Colorectal Cancer Spheroids as an In Vitro Tool for Antiangiogenic Potential Evaluation of Nanoparticles - Carvalho, Suzana [UNESP]; Silveira, Maria José; Domingues, Mariana; Ferreira, Bárbara; Pereira, Catarina Leite; Gremião, Maria Palmira [UNESP]; Sarmento, Bruno (Wiley, 2023)
The encapsulation of bevacizumab (BVZ), angiogenesis inhibitor antibody, into nanocarriers is explored aiming at enhancing its efficacy in colorectal cancer (CRC) treatment while eliminating potential side effects. Still, the translation of such nanomedicines into clinics is not straightforward owing to their preclinical screening in simplistic models, that do not mimic the complexity and heterogeneity of the CRC microenvironment. Herein, the development of a multicellular spheroid of CRC as an advanced preclinical model of CRC capable of screening the antiangiogenic potential of novel nanomedicines is proposed. For that, a quadruple co-culture is established through the combination of HCT116 cells, human pulmonary microvascular endothelial cell (HPMEC), fibroblasts, and macrophages. It is demonstrated that the developed model displays intrinsic CRC features, such as the organization of cells, expression of tumor microenvironment, extracellular matrix, and the formation of a necrotic core. Moreover, the model is shown to be composed mostly of HCT116 (93%), followed by hypoxia-inducible factor (3%), HPMEC (3%), and macrophages (1%). Gellan gum/chitosan nanoparticles encapsulating BVZ exhibit superior antiangiogenic properties when compared to free BVZ. Overall, the developed nanoparticles can further be explored as a promising approach in CRC treatment.
Keywords: angiogenesis; bevacizumab; colorectal cancer; drug delivery; multicellular tumor spheroids; polymeric nanoparticles; tumor microenvironment